WEB-BASED SERVICE APPOINTMENT SYSTEM APLICATION DESIGN MENGGUNAKAN METODE DESIGN SPRINT - Jehan Saptia Kurnia; Betesda Sinaga (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2024)
The automotive industry is one sector that continues to grow. With the increase in the number of motorized vehicles, the demand for vehicle maintenance and repair services increases. Currently, Aan Automobil already has a website and there is a Booking Appointment menu but this feature cannot be used. As demand for automotive services continues to increase and service appointments are still arranged conventionally by direct visits to workshops, so customers have to wait in long queues or even hours to get a service appointment. In addition, the appointment setting process is often ineffective because information about available times and types of services available is unclear. Based on the description above, it is very important to develop a Service Appointment Booking System using the Design Sprint Method. This is expected to improve service to customers and to avoid long queues, cars can be worked on directly according to schedule and the estimated completion time can be known early so that customers can manage valuable time